Relationship between Rational and Irrational Investment Decisions and Multiple Intelligence of Investors - Rathi, K. N.; Geetha, D. (International Journal of Economics and Financial Issues, 2024)
This study focuses on investors’ investment decision-making and examines the influence of multiple intelligences in investment decision-making, both rational and irrational. Multiple intelligences are a group of Intelligence with its entity and domain. Gardner suggests that the human being has different individual units of intellectual functioning. He labels these units as intelligence, each with identifiable and quantifiable aptitudes. The nine intelligence types differently influence an individual’s behaviour and decisions. The multiple intelligence Inventory and a questionnaire on investment decision-making were used for data collection from a hundred investors. Analysis was done with the help of Pearson’s correlation, multiple regression chi-square test, and correspondence analysis. Rational decision-making is intellectual, as per the review, and it is proved here that intelligence influences rational decision-making significantly while the other is not influenced. The observed results help to get new visions of investment behaviour, including a new proof of the root causes of investment decisions.